Evaluation Of The Application Of Nursing Management Related To Nursing Human Resource Planning At The Banggai Hospital - Ishak, La Ode Ismail; Kadang, Yulta; Yartin, Siti (Jurnal Ners, 2024)
Human Resources of Health (HRH), especially in nursing is one of the influencing factors of health services implementation. The HRH needs planning have purposes to ensure that the quality, placement, and availability of medical staff are in accordance to standardization. The aim of the research was to evaluate the implementation of nursing management related to Nursing Human Resources planning at Banggai General Hospital. This is qualitative research with a phenomenological approach. The method of data collection is by in-depth interviews using semi-structured interview guidelines toward 6 informants consisting of the Head of Administration and Staffing, Head of Nursing and Midwifery, Assistant Head of Nursing and Midwifery, ICU in charge, ER in charge, and VIP in charge. The sampling method used is Non Probability with purposive sampling technique. Data analysis was done by using the thematic analysis method. The results of the research found 7 themes, such as nurse recruitment policies, the competence of planning staff, managing data and information, mechanisms for achieving the nurses’ needs, methods and calculations applied, nurse staffing patterns, and follow-up planning needs. The conclusion mentioned that the implementation of nursing management related to nursing human resource planning at Banggai General Hospital has not been implemented properly. Suggestions Banggai General Hospital should coordinate immediately between departments in the implementation of nursing management in planning the achievement of nursing human resource needs.